The Impact of Distance Education on Teaching Reading and Writing Skills: A Study among First Semester Students at the Faculty of Languages at Benghazi University - H. Alawami, Abeer (مجلة كلية الاداب, 2024)
During the COVID-19 pandemic, faculty members and students had to leave their classrooms and move into online education contexts. This study has attempted to explore the effect of distance education on reading and writing skills among first semester students at English department, faculty of languages at Benghazi University. To do so, firstly, the starting point was comparing students' performance on two tests one after face to face teaching and the other after online teaching. Then a semi structured interviews were conducted with 20 students who were chosen randomly to understand the reasons behind their performance. Using Thematic Analysis (TA), students’ responses were transcribed, codified, and interpreted. The findings of TA revealed that along with several disadvantages and challenges that students experienced in distance education with regard to learning English reading and writing skills, distance learning provided some opportunities and benefits for their learning. The study also provided some solutions regarding online challenges.